2016
DOI: 10.1002/1873-3468.12346
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biophysical and functional consequences of tropomyosin–fluorescent protein fusions

Abstract: The dynamic nature of actin polymers is modulated to facilitate a diverse range of cellular processes. These dynamic properties are determined by different isoforms of tropomyosin which are recruited to distinct subpopulations of actin polymers to differentially regulate their functional properties. This makes tropomyosin an attractive target for labelling discrete actin populations. We have assessed the effect of different fluorescent labelling strategies for this protein. Although tropomyosin–fluorescent fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In the fluorescent fusion proteins, sfGFP/mCherry was linked to the N termini of the tropomyosins because such fusion proteins localize properly to the stress fiber network in cells and can rescue the knockout phenotype ( Figure S1 B) [ 7 ]. Moreover, a recent biochemical study demonstrated that an amino-terminal S. pombe tropomyosin fluorescent fusion binds actin filaments and forms similar end-to-end interactions compared to endogenous acetylated tropomyosin [ 16 ]. The actin filament co-sedimentation assay was first applied to examine the binding of non-tagged and sfGFP-tagged tropomyosins to non-muscle β/γ-actin filaments.…”
Section: Resultsmentioning
confidence: 99%
“…In the fluorescent fusion proteins, sfGFP/mCherry was linked to the N termini of the tropomyosins because such fusion proteins localize properly to the stress fiber network in cells and can rescue the knockout phenotype ( Figure S1 B) [ 7 ]. Moreover, a recent biochemical study demonstrated that an amino-terminal S. pombe tropomyosin fluorescent fusion binds actin filaments and forms similar end-to-end interactions compared to endogenous acetylated tropomyosin [ 16 ]. The actin filament co-sedimentation assay was first applied to examine the binding of non-tagged and sfGFP-tagged tropomyosins to non-muscle β/γ-actin filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence labeling of tropomyosins can impair their function, so that the effects of different labeling strategies depend on the isoform and experimental system. Fusion of a fluorescent protein tag to the N-terminus of Cdc8, the sole tropomyosin in fission yeast, does not perturb its assembly on actin filaments in vitro or localization in the cell ( Brooker et al , 2016 ) but leads to severe functional defects, in particular misregulation of actin nucleation and cell division ( Wu et al, 2003 ; Brooker et al , 2016 ). These defects can be alleviated by using certain cysteine mutants of Cdc8, and Cdc8 labeled at the engineered cysteine can assemble on actin ( Christensen et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, fluorescently labeling tropomyosins is generally problematic as mutations or insertions within the protein can potentially disrupt its coiled-coil structure ( Greenfield and Hitchcock-DeGregori, 1995 ). Additionally, tropomyosins labeled on the N- or C-terminus are not fully functional, as the presence of a label blocks end-to-end associations between tropomyosin molecules ( Brooker et al, 2016 ). Therefore, we created three distinct Cdc8 mutants, each containing an engineered cysteine mutation that could be labeled for visualization by TIRFM ( Figure 1—figure supplement 1 , Methods).…”
Section: Resultsmentioning
confidence: 99%